2016
DOI: 10.3897/jhr.49.7929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the reduction of urban lawn mowing on wild bee diversity (Hymenoptera, Apoidea)

Abstract: To analyse the effects of reduced green space management in urban areas on the biodiversity of insects, we compared intensely mowed lawns (mowed 12 times per year) with meadows under reduced maintenance (mowed only twice per year) in the city of Tübingen (Baden-Württemberg, Germany). Over the entire field season, 177 wild bee individuals representing 43 species were caught using sweep nets. Areas with reduced maintenance showed significantly higher total species numbers and biodiversity indices. Our research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Regarding the vegetation of the sites, the restoration treatments increased plant species richness by adding a considerable pool of native dry-grassland species (Fischer, von der Lippe & Kowarik, 2013) and resulted in an increased floral diversity (Senße, 2013). This is in line with a study that revealed the positive effect of increased floral diversity for bumblebee and hoverfly abundances in amenity grassland (Blackmore & Goulson, 2014) and findings of Wastian, Unterweger & Betz (2016). Whereas Hanley, Awbi & Franco (2014) showed for urban gardens that bumblebees have no dietary preference for native or non-native plants, there is also evidence from highly disturbed sites (roadverges), where restoration of the native vegetation especially resulted in increased bee richness (Hopwood, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the vegetation of the sites, the restoration treatments increased plant species richness by adding a considerable pool of native dry-grassland species (Fischer, von der Lippe & Kowarik, 2013) and resulted in an increased floral diversity (Senße, 2013). This is in line with a study that revealed the positive effect of increased floral diversity for bumblebee and hoverfly abundances in amenity grassland (Blackmore & Goulson, 2014) and findings of Wastian, Unterweger & Betz (2016). Whereas Hanley, Awbi & Franco (2014) showed for urban gardens that bumblebees have no dietary preference for native or non-native plants, there is also evidence from highly disturbed sites (roadverges), where restoration of the native vegetation especially resulted in increased bee richness (Hopwood, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…This initiative has been dubbed ''No Mow May'' and led researchers to follow up with an ''Every Flower Counts'' community initiative to document which flowers were common to their blooming lawns. Additionally, previous work has shown that reducing mowing intensity will have positive impacts on urban bee abundance and diversity (Lerman et al, 2018, Wastian et al 2016 but it remains unclear how generalizable these results are. Other initiatives that promote the creation of bee habitat in urban landscapes include the ''Lawns to Legumes'' project Minnesota (https://bwsr.state.mn.us/l2l) and the Xerces Society's and National Pollinator Network's ''Million Pollinator Garden Project'' (http://millionpollinatorgardens.org/).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study in combination with the authors' previous results (Ade et al 2012, Hiller and Betz 2014, Kricke et al 2014, Wastian et al 2016, Unterweger et al 2017b) suggest an adapted management regime under additional considerations of sink and source dynamics (e.g. Pulliam 1988, Howe et al 1991, Watkinson and Sutherland 1995 and metapopulation models (e.g.…”
Section: Adapted Mowing Concept To Stabilise and Expand Insect Populasupporting
confidence: 70%
“…The studies of these previous experimental setups (Ade et al 2012, Hiller and Betz 2014, Kricke et al 2014, Wastian et al 2016, Unterweger et al 2017b) underline the ecological value of management reduction for insect biodiversity. These studies have revealed significantly higher numbers of species and individuals on meadows cut twice a year in combination with the removal of the biomass compared with lawns cut monthly.…”
Section: Adapted Mowing Concept To Stabilise and Expand Insect Populamentioning
confidence: 99%
See 1 more Smart Citation